Clear cell stromal tumour of the lung with YAP1:TFE3 fusion: four cases including a case with highly aggressive clinical course. Issue 2 (11th July 2022) - Dehner, Carina A; Sadegh, David; Boulos, Fouad; Messias, Nidia; Wang, Wei‐Lien; Demicco, Elizabeth G; Chrisinger, John S A
Abstract : Aims: Clear cell stromal tumour of the lung (CCST‐L) is a rare, recently recognised neoplasm which has been found to express TFE3 and harbour YAP1::TFE3 fusions. Initial data suggested a benign process; however, a single reported case gave rise to distant metastases. We sought to describe the clinicopathological and molecular features of additional cases of CCST‐L. Methods and Results: Pathology and molecular archives were searched for cases of CCST‐L or tumours with YAP1::TFE3 fusions. Clinical features were noted. Available slides, including immunohistochemical studies, were re‐reviewed for diagnosis confirmation and assessment of pathological features. Results of molecular studies were also recorded. Four tumours were identified, all occurring in women (median age = 61 years, range = 24–69). Median tumour size was 4.4 cm (range = 1–9.5 cm); three tumours were unifocal and one was multifocal. Tumours were composed of epithelioid to spindled cells with eosinophilic to clear cytoplasm and grew in sheets, vague nests and short fascicles. Nuclear atypia was predominately mild; however, two cases showed scattered atypical cells. Mitotic activity was generally low, although one case showed a mitotic count of 6/2 mm 2 . All tumours expressed TFE3 and harboured YAP1::TFE3 fusions. One case was unresectable and was treated with chemotherapy, and two underwent complete resection. One patient died of disease 7 months following diagnosis, while a second patient was alive with no evidence of disease after 43 months. Follow‐up was not available for two cases. Conclusion: CCST‐L expresses TFE3, harbours YAP1::TFE3 fusions and at least rare cases behave in an aggressive manner. Abstract : Imaging and biopsy findings from case 1. A, Multiple bilateral lung lesions are seen (computed tomography). Core biopsy specimen shows a proliferation of eosinophilic to clear cells growing in vague packets (B) and scattered intratumoral foamy histiocytes (C). D, The tumour is strong and diffusely positive for TFE3.